Economic condition of the manobos in barangay Manobo, Magpet, North Cotabato then and now - Coresis, Ma. Katrina
This is a research study on the economic condition of the Manobos before and after the entry of the different agents of modernization. It focused on the changes brought about by the logging operations and other agents, upon the economic life of the Manobos and their way of responding to these changes. Colonization has brought about major changes in the native economy. Among these change agents, it is the logging operations that greatly affected the people especially those whose lives are deeply entrenched in the forest ? the indigenous people. By 1960's, Barangay Manobo was not exempted with the influx of migrant settlers and logging concessionaires. As a result of the depletion of forest resources, the traditional hunting and gathering activity of the early Manobos was replaced with ecologically sustainable slash and burn system for self-provisioning. Moreover, with the interaction between the lowlanders and the Manobos, the later develop a taste for consumer goods. Subsequently, this prompted the Manobos to enter into a kind of trading with the lowlanders to generate money through the surplus production of crops. These crops include, Tahiti(an indigenous plant used in making soft-broom), abaca, coffee, banana, and vegetables. At present majority of the Manobos in the area engaged in farming however, the traditional economic activities still continue to exist side by side with surplus-oriented mode of production. In order to facilitate the financial assistance given by the government for their livelihood projects, they organize themselves into community organizations and cooperatives. Despite the government projects and policies channeled through these organizations, they are not enough to bring about significant improvement in the economic lives of the Manobos. There is still much to be done.